Déclinaison d’une base de données 3D – Sur les pas de Breuil, une visite virtuelle de Lascaux - Valérie Feruglio; José Péral; Norbert Aujoulat (In Situ)
In this article we present the example of a multimedia product of the Lascaux cave 3D database prepared for presentation to the general public. This database was first established for purposes of study and conservation. The steps undertaken in the creation of the product and the actors and the technical means employed are analysed. The project is designed to underpin the specifications prior to 3D scanning of the site, specifications drawn up by archaeologists to ensure that the project will take into account budgetary considerations and the appropriate choice of resolution and definition.